Sensitivity Plot of cy:(m4 + 3*m3)*10-4 - Cycle of Money - Challoumis, Constantinos (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this work, escape savings are less common than financial liquidity. A factor of ten greater than escape savings is the velocity of financial liquidity. It uses mathematical definitions by the cycle of money and shows the sensitivity plot of cy: (m4 + 3*m3)*10-4. This is an instance where the money cycle and financial liquidity are the same. The results show that the power of the velocity of financial liquidity is substantially larger than the velocity of escape savings (resulting in the same outcome for one, two, or three times higher power), the money cycle and financial liquidity are equivalent. S.M. (Sensitivity Method) is the method that is used. The objective of the methodology is to confirm using the current equation via a case study, with the scope to clarify the money cycle.